Enhancing judicial skills in domestic violence cases: the development, implementation, and preliminary evaluation of a model US programme. Issue 4 (2nd October 2018) - Jaffe, Peter G; Crooks, Claire V; Reid, Maureen; White, Jennifer; Pugh-Markie, Danielle; Baker, Linda
ABSTRACT: The overwhelming number and complexity of domestic violence cases in criminal and family courts has resulted in the development of education programmes to assist judges. There is limited research on judicial education in this area. This paper reviews one such initiative entitled 'Enhancing Judicial Skills in Domestic Violence Cases' (EJS) that has been developed and implemented over the last 20 years by the National Judicial Institute on Domestic Violence, a partnership of the US Department of Justice Office on Violence Against Women, National Council of Juvenile and Family Court Judges and Futures Without Violence. We present findings of a preliminary evaluation of the programme based on the self-reports of 480 judges who had taken the four-day workshop between 2006 and 2010. Overall, judges reported the programme to be engaging and effective. At a six-month follow‐up, most of the judges identified specific benefits and behavior changes in the areas of access to justice, judicial leadership, victim safety, and abuser accountability as a result of participating in the programme. Critical issues in judicial education are highlighted based on the authors' experiences in the development and implementation of this programme.